Human and companion animal Proteus mirabilis sharing - Marques, Cátia (2022)
Proteus mirabilis is an important pathogen that is associated with urinary tract infections. This study aims to determine the colonization and sharing of P. mirabilis between healthy companion animals and humans that are living together and to evaluate the clonal relatedness of the fecal and clinical stains. Eighteen households (24 humans, 18 dogs, 8 cats) with at least one human–animal pair were studied. Fecal samples were plated onto MacConkey and Hektoen agar and P. mirabilis PFGE analysis (NotI; Dice/UPGMA; 1.5% tolerance) was conducted for the households with multiple positive participants. Antimicrobial-resistance was tested according to CLSI. The fecal P. mirabilis pulse-types were compared with uropathogenic clinical strains (n = 183). Forty-nine P. mirabilis were isolated from eight households. The percentage of colonization in the dogs (44.4%, n = 8/18) was significantly higher (p = 0.0329) than in the humans (12.5%, n = 3/24). Three households had multiple colonized participants. One human–dog pair shared related P. mirabilis strains, which clustered with a clinical strain of animal origin (82.5%). One fecal P. mirabilis strain, from a dog, clustered with two human community-acquired clinical strains (80.9%, 88.9%). To our knowledge, this is the first report of dogs and humans living in close contact and sharing related P. mirabilis strains. The high frequency of colonization in the dogs underlines their possible role as P. mirabilis reservoirs for humans and other dogs.